2016
DOI: 10.1007/s40336-016-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of 90Y-radioembolization in downstaging primary and secondary hepatic malignancies: a systematic review

Abstract: Radioembolization (RE) is an emerging treatment strategy for patients with primary hepatic malignancies and metastatic liver disease. Though RE is primarily performed in the palliative setting, a shift toward the curative setting is seen. Currently, hepatic resection and in selected cases liver transplantation are the only curative options for patients with a hepatic malignancy. Unfortunately, at diagnosis most patients are not eligible for liver surgery due to the imbalance between the necessary liver resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 110 publications
(186 reference statements)
0
22
0
Order By: Relevance
“…An FLR and TLV ratio of 20-30% has been suggested as a threshold for patients with normal liver parenchyma and 40-45% for patients with liver cirrhosis [35]. To date, the impact of RE-induced contralateral liver hypertrophy has been assessed in two systematic reviews, including seven and eight studies, respectively [10,17]. Teo et al reported only the relative degree of hypertrophy regardless of the oncological outcome, and no data on the ratio of FLR to TLV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An FLR and TLV ratio of 20-30% has been suggested as a threshold for patients with normal liver parenchyma and 40-45% for patients with liver cirrhosis [35]. To date, the impact of RE-induced contralateral liver hypertrophy has been assessed in two systematic reviews, including seven and eight studies, respectively [10,17]. Teo et al reported only the relative degree of hypertrophy regardless of the oncological outcome, and no data on the ratio of FLR to TLV.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection after radioembolization was carried out in 109 out of 362 patients (30%). Although the available data suggest that radioembolization prior to major hepatectomy is safe with a promising oncological outcome, the definitive role of radioembolization requires assessment within controlled clinical trials.Cancers 2020, 12, 294 2 of 14 results for ALPPS in patients with primary liver malignancies have been disappointing due to high perioperative morbidity and mortality rates [8].Recently, there has been increasing interest in radioembolization with 90 Y-microspheres (also known as selective internal radiation therapy), as this treatment offers local tumor control with simultaneous hypertrophy of the contralateral lobe [9,10]. Radioembolization (RE) is a minimally invasive procedure with transarterial delivery of 90 Y-loaded microspheres made of glass (diameter: 25 ± 10 µm; activity per particle: 2500 Bq) or resin (diameter: 35 ± 10 µm; activity per particle: 50 Bq) [11,12].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(7) In systematic review, Braat et al, presented studies that showed evidences of benefits of neodjuvant use of TARE in intra-hepatic colangiocarcinoma, in addition to hepatocarcinoma. (9) There were no cases of progression of the disease during time of waiting for surgical intervention. All patients reported to be with an accompanying person (mean of 25.6 months after definitive surgical treatment; ranging from 8 to 35 months) and without recurrent of the disease.…”
Section: Discussionmentioning
confidence: 93%